2022
DOI: 10.1177/23328584221096465
|View full text |Cite
|
Sign up to set email alerts
|

Community-Centered School Leadership: Radical Care andAperturasDuring COVID-19

Abstract: We share school leaders’ perspectives on Zoom videos concerning the needs of immigrant and refugee families in Title I schools. In these videos, participants crafted and shared personal narratives about their leadership experiences during the COVID-19 era of education. Rooted in participatory design research methods, the process of designing these videos were both a research project and an intervention to assist families and school leaders to better understand each other. We present a close analysis of adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Researchers have also illuminated the marginalization of undocumented and immigrant communities in Utah, along with how these youth, families and community members attempt to resist anti-immigrant sentiments and educational exclusion (Alvarez Guti errez, 2015;Cahill et al, 2016;Hernandez et al, 2023). The COVID-19 pandemic and shift to online learning also led to an exacerbation of social isolation and inequality experienced by CLD families and students in SLC during the 2020-2021 school year as many struggled to access basic needs, such as food and healthcare (Alvarez Guti errez et al, 2022). Finally, and most recently, the U.S. Department of Justice, Civil Rights Division (2021) found that employees in Utah's Davis School District intentionally contributed to the discrimination of Black students by failing to provide an equal or safe environment for its Black learners.…”
Section: Literature Review Race and Education In Utahmentioning
confidence: 99%
“…Researchers have also illuminated the marginalization of undocumented and immigrant communities in Utah, along with how these youth, families and community members attempt to resist anti-immigrant sentiments and educational exclusion (Alvarez Guti errez, 2015;Cahill et al, 2016;Hernandez et al, 2023). The COVID-19 pandemic and shift to online learning also led to an exacerbation of social isolation and inequality experienced by CLD families and students in SLC during the 2020-2021 school year as many struggled to access basic needs, such as food and healthcare (Alvarez Guti errez et al, 2022). Finally, and most recently, the U.S. Department of Justice, Civil Rights Division (2021) found that employees in Utah's Davis School District intentionally contributed to the discrimination of Black students by failing to provide an equal or safe environment for its Black learners.…”
Section: Literature Review Race and Education In Utahmentioning
confidence: 99%
“…When the pandemic spread in early 2020, teachers were forced to work at the “front-line” to keep schools running ( Hart & Nash, 2020 ). They had to quickly and efficiently become agile policy actors to implement rapidly changing school policies and effective learners to attain new knowledge and skills for online and hybrid classes, all while acting as dedicated caregivers and supporting the diverse needs of students and their communities ( Alvarez Gutiérrez et al, 2022 ; Anderson et al, 2020 ; Authors, 2021a ). In addition to the daily infection-related health risks teachers took on in doing their jobs, these multiple demands further increased the emotional and physical burdens of teaching across the world ( Sokal et al, 2020 ; Wong & Moorhouse, 2020 ).…”
Section: Introductionmentioning
confidence: 99%